Design and implementation of interface circuitry for CMOS-based SAW gas sensors - Yasin, F. M.; Reaz, M. B. I.; Tye, K. F. (IEEE, 2005)
The design and development of interface circuitries for CMOS-based SAW gas sensor is presented in this paper. The SAW sensor devices typically run at RF, requiring most design to have complex signal conditioning circuitry. Our approach attempt to design a simple architecture with reduced power consumption. The SAW sensors operate at 354MHz. Simulation data show that the interface circuitries are ten times smaller with lower power supply, compare to existing work.